Clinical Approaches to Minimize Readmissions of Patients with COPD: A Narrative Review - Duong-Quy, Sy; Vo-Pham-Minh, Thu; Duong-Thi-Thanh, Van; Craig, Timothy; Nguyen-Nhu, Vinh (Current Respiratory Medicine Reviews, 2023)
Chronic Obstructive Pulmonary Disease (COPD) is a progressive disease and also a leading cause of morbidity and mortality worldwide. The frequent readmissions of patients with COPD may reduce lung function, mental health, and quality of life; it also increases the cost of treatment and mortality rate. Some common factors that may increase the readmission frequency of COPD patients include delay of diagnosis, advanced lung function decline, lack of adherence for COPD treatment, ineffective management of comorbidities, acute exacerbation or stable COPD, and infections. However, these factors might be well controlled with appropriate approaches to minimize the readmission of patients with COPD. In this review, we propose a strategy with a seven-step approach to reduce the readmission in COPD patients, including early diagnosis of COPD, optimal treatment for stable COPD, targeted management of comorbidities, adequate therapy for acute exacerbations, individualized action plans for COPD patients, effective prevention of bacterial and viral infections, and adaptive program of pulmonary rehabilitation. Thus, implementing this approach may reduce the risk of readmission in patients with COPD.
Keywords: acute exacerbation